The Role of the Education Office in Increasing Public Interest in Public Schools - Sabriana Sabriana; Suyatno Suyatno; Widodo Widodo (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2024)
The focus of this research is to analyze using literature studies on the strategies and policies of the Education Office in increasing public interest in entering public schools so that it is expected to have a positive impact so that the Education Office in the regions, especially areas that experience a decrease in the number of students and are constrained to increase students in the process of accepting new students. The method used in this study is the literature study method. The literature study method, also known as literature study, is a technique for collecting data and information by examining written sources such as scientific journals, reference books, encyclopedias, and other reliable sources either in written form or in digital formats that are relevant and related to the object being researched. Increasing public interest in attending public schools is a challenge that the Education Office must face as a government agency responsible for the implementation of education in the regions. Through a comprehensive strategy, including improving the quality of education, increasing access and equity in education, as well as improving the image and reputation of public schools, the Education Office can play a strategic role in encouraging community participation to take advantage of public education services. This effort will impact the quality of education and the development of superior and competitive human resources in the future. The Education Office's policy of increasing public interest in attending public schools is an important and strategic effort. Through various comprehensive policies, such as improving the quality of public schools, expanding access and capacity, as well as socialization and providing incentives, the Education Office can realize the goal of equitable distribution and improvement of the quality of education at all levels of society.